Expression and characterization of recombinant human lactoferrin in edible alga Chlamydomonas reinhardtii. Issue 5 (4th May 2019) - Pang, Xiaonan; Tong, Yuxi; Xue, Wenzhi; Yang, Yi-feng; Chen, Xiwen; Liu, Jia; Chen, Defu
ABSTRACT: Lactoferrin (LF) is a naturally occurring iron-binding glycoprotein with a variety of biological functions. It has increasing demand every year and huge market potential. In this study, we explored the feasibility of expressing human LF (hLF) in edible algae C. reinhardtii . A codon-optimized hLF gene was synthesized, inserted into pCAMBIA-1301C and transformed into C. reinhardtii SP strain. In total, 7 hLF -expressing clones were selected with clone 121 exhibiting the highest expression level. The hLF-containing algal extract significantly inhibited the growth of bacteria such as Escherichia coli and Klebsiella variicola . During acute toxicity experiment no acute toxicity was detected, especially on changes of the body weight and histopathology of organs. The recombinant hLF possessed a similar or modestly reduced stability compared to commercial hLF standard. Our data indicated that expression of hLF in C. reinhardtii is feasible and paved a way to commercial production of lactoferrin using edible Chlamydomonas expression system. Abbreviations : atrazine chlorohydrolase gene (atzA); bovine serum albumin (BSA); human LF (hLF); lactoferrin (LF); Luria-Bertani (LB); quantitative reverse transcriptase PCR (qRT-PCR) ; SDS polyacrylamide gel electrophoresis (SDS-PAGE); Tris-acetate phosphate (TAP); western blotting (WB) Graphical abstract: : Expression of human lactoferrin in Chlamydomonas reinhardtii had significant antibacterial activity, stable physical-chemical property and no acute toxicity to mice.